Neurofibromatosis Type 1–Associated MPNST State of the Science: Outlining a Research Agenda for the Future. (22nd August 2017) - Reilly, Karlyne M.; Kim, AeRang; Blakely, Jaishri; Ferner, Rosalie E.; Gutmann, David H.; Legius, Eric; Miettinen, Markku M.; Randall, R. Lor; Ratner, Nancy; Jumbé, N. L.; Bakker, Annette; Viskochil, David; et al.
Abstract: Malignant peripheral nerve sheath tumor (MPNST) is an aggressive soft tissue sarcoma for which the only effective therapy is surgery. In 2016, an international meeting entitled "MPNST State of the Science: Outlining a Research Agenda for the Future" was convened to establish short- and long-term research priorities. Key recommendations included the: 1) development of standardized, cost-efficient fluorodeoxyglucose positron emission tomography and whole-body magnetic resonance imaging guidelines to evaluate masses concerning for MPNST; 2) development of better understanding and histologic criteria for the transformation of a plexiform neurofibroma to MPNST; 3) establishment of a centralized database to collect genetic, genomic, histologic, immunohistochemical, molecular, radiographic, treatment, and related clinical data from MPNST subspecialty centers in a standardized manner; 4) creation of accurate mouse models to study the plexiform neurofibroma-to-MPNST transition, MPNST metastasis, and drug resistance; 5) use of trial designs that minimize regulatory requirements, maximize availability to patients, consider novel secondary end points, and study patients with newly diagnosed disease. Lastly, in order to minimize delays in developing novel therapies and promote the most efficient use of research resources and patient samples, data sharing should be incentivized.